1999
DOI: 10.1515/bc.1999.151
|View full text |Cite
|
Sign up to set email alerts
|

Role of p52 (NF-kappaB2) in LPS Tolerance in a Human B Cell Line

Abstract: Cells of the weakly CD14 positive human B cell line RPMI 8226, clone 1, will mobilize NF-B (p50/p65 and p50/p50) proteins and produce TNF mRNA when stimulated with lipopolysaccharide (LPS). When such cells are precultured with a low amount of LPS (50 -250 ng/ ml) for 3 -4 days followed by a secondary stimulation with a high dose of LPS (1 g/ml) then the cytokine expression is strongly reduced, i. e. the cells have become tolerant.Western blot analysis of proteins of the NF-B/rel family demonstrates cytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Recently, it was confirmed that NF-B regulates HIF-1␣ at the transcriptional level (14). Wedel et al (33) analyzed the role of different members of the transcription factor NF-B superfamily for the induction of endotoxin tolerance in more detail. They found an up-regulation of the p52 protein and its precursor p100/RelB after induction of LPS tolerance in a human B cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was confirmed that NF-B regulates HIF-1␣ at the transcriptional level (14). Wedel et al (33) analyzed the role of different members of the transcription factor NF-B superfamily for the induction of endotoxin tolerance in more detail. They found an up-regulation of the p52 protein and its precursor p100/RelB after induction of LPS tolerance in a human B cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have previously shown that CD4 ϩ T cells from mice tolerized in vivo express qualitative alterations in the composition of the NF B complex (13). Defective NF B expression is also a feature of tolerant B cells (14,15).The NF B family consists of five members, p65, c-rel, RelB, p105/p50, and p100/p52, and the NF B complex is formed by hetero-or homodimerization of these different proteins (16). p65, c-rel, and RelB are synthesized as mature proteins and contain transactivation domains, whereas p105/p50 and p100/ p52 are produced as inactive precursor proteins and lack transactivation domains.…”
mentioning
confidence: 99%
“…In addition, we have previously shown that CD4 ϩ T cells from mice tolerized in vivo express qualitative alterations in the composition of the NF B complex (13). Defective NF B expression is also a feature of tolerant B cells (14,15).…”
mentioning
confidence: 99%
“…The mechanisms underlying the induction of macrophage tolerance have been the subject of intense study, particularly with respect to TLR ligands. Some of the mechanisms that have been implicated in this process include down-regulation of TLR4 (37); decreased expression of postreceptor signaling molecules, such as the interleukin-1 receptor-associated kinase (IRAK) (32); alterations in the association between TLR5 and downstream signaling molecules (34); increased expression of proteins that block TLR signal transduction, such as IRAK-M, the macrophage-specific, kinase-deficient member of the IRAK family (27), and SOCS-1 (suppressor of cytokine signaling 1) (26,36); and, finally, upregulation of the p50 and p52 subunits of the NF-B transcription factor (24,51). Although the exact physiologic significance of macrophage tolerance is not clear, it may be important in limiting the extent and duration of inflammatory responses.…”
mentioning
confidence: 99%